Analysis of the Muroja'ah 'Ammah Program in Increasing the Learning Motivation of Students at TMI Al-Amien Prenduan Sumenep - Iwan Prayoga; Musleh Wahid (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
Muroja'ah 'Ammah or Daily Tests are part of the evaluation which is a process that includes measurement and testing, containing decision-making about grades. Daily tests are the first evaluation for students. This study uses a qualitative research method. This research is included in field research (case study) this research is field research that requires researchers to go directly to the field to get an analysis of what actually happens in the environment. The results of this study are. Improving the Learning Motivation of Students. The impact of Muroja'ah 'Ammah is to help Improve the Learning Motivation of Students. And especially to ensure that the process of implementing learning activities is running well in accordance with the desired goals. While the learning evaluation itself aims to ensure that the activities that have been carried out in the learning process are in accordance with the objectives or not. Then, the results can be used as input for planning the next program. Muroja'ah 'Ammah or Daily Tests are part of the evaluation which is a process that includes measurement and testing, containing decision-making about grades. Daily tests are the first evaluation for students. This study uses a qualitative research method. This research is included in field research (case study) this research is field research that requires researchers to go directly to the field to get an analysis of what actually happens in the environment. The results of this study are. Improving the Learning Motivation of Students. The impact of Muroja'ah 'Ammah is to help Improve the Learning Motivation of Students. And especially to ensure that the process of implementing learning activities is running well in accordance with the desired goals. While the learning evaluation itself aims to ensure that the activities that have been carried out in the learning process are in accordance with the objectives or not. Then, the results can be used as input for planning the next program.